Nitric oxide in the nervous system - Vincent, Steven R (Neuroscience perspectives, 1995)
The gas nitric oxide (NO) has burst upon neuroscience only recently, and yet it has permeated into almost every avenue of current research. The unique properties of this novel messenger have revolutionized our way ofthinking about neurotransmission. These special properties have also lead neuroscientists to invoke NO to explain many previously unexplained phenomena in neurobiology. Fortunately, the development of numerous pharmacological agents is now allowing thesehypotheses to be tested.This volume will provide a synopsis of what is now known about NO. How and where NO is produced, how it acts at the molecular level to activate the synthesis of cGMP, and the possible targets of cGMP in the nervous system are reviewed. The roles of theNO/cGMP signal transduction pathway in the central and peripheral nervous systems, in glial cells, and in neuropathology are then explored. Together, these reviews will lead to further work explaining the varied functions of NO. Key Features* Describes how and why NO is produced in the nervous system* Examines all that is known of NOs role as a neurotransmitter* Explores cellular actions and physiological roles in the brain and peripheral nervous systemCovers NOs molecular synthesis to its role in neuropathology